The return of great power war cenarios of systemic conflict between the united states and china - Heath, Timothy R.; Gunness, Kristen; Finazzo, Tristan (RAND, 2022)
Through a careful synthesis of current and historical data on relevant factors, anticipated trends, and research-grounded speculation, the authors analyze several scenarios of systemic U.S.-China conflict under hypothetical conditions in which China has neared the point of global primacy. Drawing on academic and research findings regarding the potential trajectory of international security and warfare in coming years, China's approach to future warfare, relevant experiences of preceding great powers, and historic patterns in interstate wars, they explore the possibility of a U.S.-China war of power transition. The authors develop two scenarios of systemic U.S.-China conflict. The first scenario features a low-intensity conflict that unfolds across much of the world, across many domains and over many years. The second features a high-intensity war that evolved out of the low-intensity war. The high-intensity war scenario envisions aggressive actions by both countries to destroy the war-fighting capability of the adversary and carries an extremely high risk of escalation to the most destructive levels. Both scenarios occur within the context of a deeply fragmented international situation in which the U.S. and Chinese militaries experience immense strain from sustaining the war effort while grappling with an array of nontraditional threats and responding to demands for aid from embattled partners. Although their analysis concerns a hypothetical conflict situation in which China had neared global primacy, their findings could inform defense planning for potential contingencies even today
Title from PDF document (title page; viewed August 10, 2022)
"Prepared for the U.S. Department of Defense
"RAND NATIONAL DEFENSE RESEARCH INSTITUTE
Keywords: Sicherheitspolitik; Vorherrschaft; Geopolitik; Militärpolitik; Außenbeziehungen; Konflikt; USA; China; Low-intensity conflicts (Military science); Security, International; United States / Foreign relations / China; China / Foreign relations / United States; Diplomatic relations; United States